Formaldehyde free tannin-based adhesive with epoxy as hardener for plywood - Liu, Bowen; Zhou, Yunxia; Essawy, Hisham; Chen, Qian; Liang, Jiankun; Zhou, Xiaojian; Zhang, Jun; Du, Guanben (Maderas. Ciencia y Tecnología, 2022)
A renewable tannin-based resin adhesive with enhanced bonding strength, good water resistance and long storage life has been prepared based on tannin, furfural and furfuryl alcohol coming from forest and agricultural products. Fourier transform infrared spectroscopy (FT-IR), Electrospray ionization mass spectroscopy (ESI-MS) and Differential scanning calorimetry (DSC) indicated that furfuryl alcohol and furfural can react with tannin under acidic conditions, with the involvement of –CH2–O– groups in the cross-linking of tannin-furfuryl alcohol-furfural resin (TFF) adhesive. The gel time of TFF was longer than that of tannin-furfural resin (TF), while the shear strength of TFF-bonded plywood suggested that the cured TFF adhesive acquired a performance superior to that of tannin (T) and TF adhesives. Furthermore, water resistance of TFF adhesive could be further enhanced with respect to T and TF adhesives through cross-linking with 3 % epoxy resin (EPR).